2019
DOI: 10.1108/jarhe-09-2019-0241
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude and leadership in higher education institutions

Abstract: Purpose The purpose of this paper is to examine the relationship between gratitude and transformational leadership among university teachers. The study also intended to investigate the mediating effect of social intelligence (SI) on this relationship between gratitude and leadership. Design/methodology/approach Correlation and regression are used to analyze the relationship between gratitude, SI and leadership. Mediating effect of SI is accessed using Baron and Kenny’s (1986) method and bootstrapping techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…For instance, a company may choose to institutionalize gratefulness. Now they may hire a trainer, who shall use different gratitude interventions such as daily gratitude journals, gratitude letters and subsequent visits, cultivating mindfulness, gratitude collages, self-introspection, sharing positive events, acts of kindness, gratitude guided meditation and progressive muscle relaxation techniques to imbibe habit and virtue of gratefulness among employees (Froh et al , 2008; Froh et al , 2007; Langer, 2014; Langer et al , 2010; Garg and Gera, 2019; Shapiro et al , 2002). Management and leadership play an important role in such fundamental paradigm shift in organizational change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a company may choose to institutionalize gratefulness. Now they may hire a trainer, who shall use different gratitude interventions such as daily gratitude journals, gratitude letters and subsequent visits, cultivating mindfulness, gratitude collages, self-introspection, sharing positive events, acts of kindness, gratitude guided meditation and progressive muscle relaxation techniques to imbibe habit and virtue of gratefulness among employees (Froh et al , 2008; Froh et al , 2007; Langer, 2014; Langer et al , 2010; Garg and Gera, 2019; Shapiro et al , 2002). Management and leadership play an important role in such fundamental paradigm shift in organizational change.…”
Section: Discussionmentioning
confidence: 99%
“…Spirituality is a special capability that connects one with its complete self, with others, and with the complete universe” (Mitroff and Denton, 1999). Other researchers such as Ashmos and Duchon (2000), Garg and Gera (2019), Mitroff and Denton (1999), Garg (2017c) and Singh et al (2016) provided a different conceptualization of spirituality. This diversity of definitions possesses a severe challenge in the scientific exploration of spirituality (Brown, 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous researchers have argued that grateful people experience higher levels of positive emotions such as vitality, happiness, life satisfaction (Emmons and Shelton, 2002; McCullough et al , 2002). Studies have also shown that gratitude has been positively correlated with vitality, optimism and decreased state of depression in young adults (McCullough et al , 2002; Garg and Gera, 2019). Although numerous researchers including Christopher and Schlenker (2004), Deci and Ryan (2008), Kasser and Kasser (2001), Garg (2018) and Yurchisin and Johnson (2004) reported a positive association between gratitude and various constructs of positive psychology, the studies on gratitude and vitality are scared.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following Watkins et al ’s (2003) model, gratitude, for this research, is understood as having a sense of abundance, being appreciative of the contribution of others, appreciation of simple pleasures in life and acknowledgement of the importance of experiencing and expressing gratitude. Gratitude research has seen exponential increase in the past few years, including experiential research focused on gratitude interventions, as studies suggest that state and trait gratitude have significant benefits for physical and mental health (Jans-Beken et al , 2020; Sawyer et al , 2022; Garg, 2020). Research in gratitude is likely to continue and expand because it is inextricably linked to outcomes perceived as most important by people, such as happiness and hope (Witvliet et al , 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%